The gospel according to Paul Lafargue: the religion of Capital - Lara, Marina Garcia (Cadernos de Campo (São Paulo, 1991), 2023)
Paul Lafargue's work, “The Religion of Capital”, written in the late 19th century, portrays capitalism as a powerful and popular religion, emphasizing its impact on people's lives. The author employs a religious metaphor to compare the irrational worship of the economic system to traditional religious devotion. This highlights the concerns of the period, when Europe was undergoing industrial changes and exploitation of the working class intensified. Lafargue's critique of capitalism is still relevant today, particularly in terms of the persistence of inequality and the continued pursuit of profit over human needs. This work seeks to demonstrate how the content presented by Lafargue continues to be important for understanding economic systems and reinforces the need for reflections on our current system.